Quasiperiodic ELF/VLF Emissions Associated With Corresponding Pulsations of the Geomagnetic Field - Hajoš, M.; Němec, F.; Demekhov, A.; Santolík, O.; Parrot, M.; Raita, T.; Bezděková, B. (Journal of Geophysical Research: Space Physics, 2023)
International audience We present a comparison between properties of quasiperiodic (QP) extra low frequency/very low frequency emissions observed by the low-altitude DEMETER spacecraft and ultra-low frequency (ULF) geomagnetic field pulsations measured on the ground by the Canadian Array for Realtime Investigations of Magnetic Activity system of flux-gate magnetometers and by the Sodankylä Geophysical Observatory magnetometer. Altogether, we have analyzed 398 QP events observed at the times when DEMETER was close to the ground-based magnetometers. The modulation periods of the analyzed QP events were larger than 10 s and their frequency bandwidths were larger than 200 Hz. For a part of QP emissions with modulation periods about 30 s, there was a good agreement between the modulation periods and peak frequencies of ULF magnetic field pulsations measured on the ground. These QP emissions appear to be closely associated with coincident geomagnetic pulsations (QP1 type), and they represent ∼18% of the total number of analyzed QP events. No corresponding geomagnetic pulsations were identified in the remaining 82% of QP events (QP2 type). The intensity of QP1 events does not seem to correlate with the intensity of geomagnetic field pulsations, while the intensity of QP2 events increases with the integral intensity of geomagnetic field pulsations. Based on the observed association between QP emissions and geomagnetic field pulsations, we estimate the radial distance of the generation region of QP1 emissions to L ∼ 7.